Extraction and Identification of Phenolic Compounds from the Iraqi Heliotropium europaeum L. plant - Walaa H. Jasim; Maha N. Hamad (College of Pharmacy University of Baghdad, 2021)
The plants of genus Heliotropium L. (Boraginaceae) are well-known for containing the toxic metabolites called pyrrolizidine alkaloids (PAs) in addition to the other secondary metabolites. Its spread in the Mediterranean area northwards to central and southern Europe, Asia, South Russia, Caucasia, Afghanistan, Iran, Pakistan, and India, Saudi Arabia, Turkey, and over lower Iraq, Western desert. The present study includes the preparation of various extracts from aerial parts of the Iraqi plant. Fractionation, screening the active constituent, and identification by chromatographic techniques were carried out.Heliotropium  europaeum herbs were first defatted with n-hexane then extracted exhaustively by soxhlet apparatus using absolute methanol. The extract was filtered and the solvent was evaporated by applying a reduced pressure by a rotary evaporator. The residue suspended in distilled water and partitioned with chloroform, ethyl acetate,  n-butanol. The hydrolysis step was done for the two fractions (n-butanol and ethyl acetate).  Phytochemical analysis for the screening and identification of bioactive substances of the Heliotropium europaeum plant was done for each fraction. The identification of n-butanol and ethyl acetate fractions was carried out by thin-layer chromatography (TLC) and HPLC technique. For quantitive analysis, the concentration was calculated by serial concentrations of external standard materials to build a calibration curve between concentration and its equivalent peak area. The outcomes of this study were the identifications of new six phenolic compounds from H. europaeum ethyl acetate fraction, which exhibited wide biological activity. The identified compounds were kaempferol (1), Silybin (2), caffeic acid (3), Genistein (4), Apigenin (5), in addition to syringic acid (6). In the present study, we regard the first to report such results about the phenolic compounds in H. europaeum extract. A total of six discovered phenolics were identified in this extract for the first time. Our results on H. europaeum constituents provide a scientific base to examine the pharmacological effects of this plant in the future.